“Dismantling White Supremacy” in the United States: Identity and Racial Politics in Chinelo Okparanta’s Harry Sylvester Bird (Altre Modernità, 2024)
“Dismantling White Supremacy” in the United States: Identity and Racial Politics in Chinelo Okparanta’s Harry Sylvester Bird A conversation with Chinelo Okparanta(16 April 2023) [1] I would like to express my gratitude to Chinelo Okparanta for her time, kindness, and the valuable contribution she is making to the global reception of Nigerian literature.